E-commerce service quality: integrating e-servqual and Kano model - Tahany Bisyarah Ra’fat; Rahmiati; Gesit Thabrani (Universitas Negeri Padang, 2021)
This study aims to: (1) analyze the quality of services provided by e-commerce (2) determine the priority level of attributes for customer satisfaction. This research is descriptive research. The population of this study is the people of Padang City who have shopped more than 2 times through e-commerce. The research sample was determined based on a non-probability method and purposive sampling technique. The total sample was 330 people. The data used are primary data obtained from online questionnaires. The analytical method used is descriptive analysis. This research was analyzed using SPSS v21 software. The results of this study indicate that 17 e-servqual attributes fall into the One Dimensional category and four attributes fall into the must be category.